Skeletal Problems in Sickle Cell Anemia Children - Siraj Nabi, Suresh Kumar, Tauseef Raza, Muhammad Kaleem Khan, Osama Bin Zia, Muhammad Faisal Bashir (Pakistan Journal of Medical & Health Sciences, 2023)
Background and objective: Red blood cells in sickle cell anemia (SCA) take on an unnatural, stiff, sickle-shaped appearance. The musculoskeletal problems of sickle cell anemia (SCA) stem from the fact that blood vessels get blocked, which causes tissue ischemia, infarction, and gradual damage to end organs. The researchers in this study set out to identify common musculoskeletal problems in children diagnosed with SCA. Methods: In this retrospective study, 140 children with sickle cell anemia were included. Musculoskeletal problems, subject age, and gender make up the variables that are examined. In order to compare means, we utilized the Mann Whitney U-test, and to check for significant associations between categorical variables, we utilized Fisher’s exact. For statistical significance, a P-value lower than 0.05 was considered. Results: Among all, 86 (61.4%) were males and 54 (38.6%) were females. 3 (2.1%) cases had age < 1years, 45 (32.1%) cases had age 1-5 years, 60 (42.9%) cases had age 6-10 years and 32 (22.9%) had age 11-15 years. Pain bone crisis 55 (39.3%) was the most common cause of musculoskeletal disorder. Frequency of mortality was 10 (7.1%). Physiotherapy referrals were 13 (9.3%). Conclusion: Due to the fact that sickle cell disease affects more individuals than expected, screening is not widespread, and clinically proven, multidisciplinary treatment is scarce, many people are poorly managed. Musculoskeletal complaints can be treated with physiotherapy, although its relationship to the underlying condition is rarely acknowledged. Keywords: Physiotherapy, Musculoskeletal complications, Sickle cell anaemia,